Cover crops and fall residual herbicides for managing Italian ryegrass - Jose H.S. de Sanctis; Charles W. Cahoon; Wesley J. Everman; Travis W. Gannon; Katherine M. Jennings; Zachary R. Taylor; Brock A. Dean; Jacob C. Forehand; James H. Lee (Weed Technology)
North Carolina growers have long struggled to control Italian ryegrass, and recent research has confirmed that some Italian ryegrass biotypes have become resistant to nicosulfuron, glyphosate, clethodim, and paraquat. Integrating alternative management strategies is crucial to effectively control such biotypes. The objectives of this study were to evaluate Italian ryegrass control with cover crops and fall-applied residual herbicides and investigate cover crop injury from residual herbicides. This study was conducted during the fall/winter of 2021–22 in Salisbury, NC, and fall/winter of 2021–22 and 2022–23 in Clayton, NC. The study was designed as a 3 × 5 split-plot in which the main plot consisted of three cover crop treatments (no-cover, cereal rye at 80 kg ha−1, and crimson clover at 18 kg ha−1), and the subplots consisted of five residual herbicide treatments (S-metolachlor, flumioxazin, metribuzin, pyroxasulfone, and nontreated). In the 2021–22 season at Clayton, metribuzin injured cereal rye and crimson clover 65% and 55%, respectively. However, metribuzin injured both cover crops ≤6% in 2022–23. Flumioxazin resulted in unacceptable crimson clover injury of 50% and 38% in 2021–22 and 2022–23 in Clayton and 40% in Salisbury, respectively. Without preemergence herbicides, cereal rye controlled Italian ryegrass by 85% and 61% at 24 wk after planting in 2021–22 and 2022–23 in Clayton and 82% in Salisbury, respectively. In 2021–22, Italian ryegrass seed production was lowest in cereal rye plots at both locations, except when it was treated with metribuzin. For example, in Salisbury, cereal rye plus metribuzin resulted in 39,324 seeds m–2, compared to ≤4,386 seeds m–2 from all other cereal rye treatments. In 2022–23, Italian ryegrass seed production in cereal rye was lower when either metribuzin or pyroxasulfone were used preemergence (2,670 and 1,299 seeds m–2, respectively) compared with cereal rye that did not receive an herbicide treatment (5,600 seeds m–2). cereal rye (Secale cereale L.) and crimson clover (Trifolium incarnatum L.)